Tumor Necrosis Factor Alpha Inhibits L-Type Ca2+ Channels in Sensitized Guinea Pig Airway Smooth Muscle through ERK 1/2 Pathway - Jorge Reyes-García; Edgar Flores-Soto; Héctor Solís-Chagoyán; Bettina Sommer; Verónica Díaz-Hernández; Luz María García-Hernández; Luis M. Montaño (Hindawi Limited, 2016)
Tumor necrosis factor alpha (TNF-α) is a potent proinflammatory cytokine that plays a significant role in the pathogenesis of asthma by inducing hyperresponsiveness and airway remodeling. TNF-α diminishes the L-type voltage dependent Ca2+ channel (L-VDCC) current in cardiac myocytes, an observation that seems paradoxical. In guinea pig sensitized tracheas KCl responses were lower than in control tissues. Serum from sensitized animals (Ser-S) induced the same phenomenon. In tracheal myocytes from nonsensitized (NS) and sensitized (S) guinea pigs, an L-VDCC current (ICa) was observed and diminished by Ser-S. The same decrease was detected in NS myocytes incubated with TNF-α, pointing out that this cytokine might be present in Ser-S. We observed that a small-molecule inhibitor of TNF-α (SMI-TNF) and a TNF-α receptor 1 (TNFR1) antagonist (WP9QY) reversed ICa decrease induced by Ser-S in NS myocytes, confirming the former hypothesis. U0126 (a blocker of ERK 1/2 kinase) also reverted the decrease in ICa. Neither cycloheximide (a protein synthesis inhibitor) nor actinomycin D (a transcription inhibitor) showed any effect on the TNF-α-induced ICa reduction. We found that CaV1.2 and CaV1.3 mRNA and proteins were expressed in tracheal myocytes and that sensitization did not modify them. In cardiac myocytes, ERK 1/2 phosphorylates two sites of the L-VDCC, augmenting or decreasing ICa; we postulate that, in guinea pig tracheal smooth muscle, TNF-α diminishes ICa probably by phosphorylating the L-VDCC site that reduces its activity through the ERK1/2 MAP kinase pathway.